(untitled) (Politeja, 2024)
ENLARGEMENT PERSPECTIVE AND REFORM OF THE EUROPEAN UNION Enlargement policy is one of the most important in the functioning of the European Union (formerly the European Communities). Since the first accessions in the 1970s, the admission of new countries has been accompanied by actions aimed at reforming the EC (EU). Some of them ended in failure, but the connection between enlargement and reforms, which de facto meant deepening integration, is very clear. In the third decade of the 21st century, the enlargement process is being continued. And as with previous enlargements, attempts to reform the EU will undoubtedly be made now. However, this time it may prove even more difficult to implement them than in the past. Therefore, the main goal of this article is to try to answer the question of whether it is possible – and if so, how – to introduce reforms in the EU that would pave the way for the admission of new countries. In the absence of the possibility of revising the treaties on which the functioning of the EU is based, four variants of solving such an impasse and introducing changes in the functioning of the EU are theoretically possible. However, some of them are difficult and may actually represent very significant changes in the character of the EU.